Gonadectomy in conditions affecting sex development: a registry-based cohort study - (:unkn) unknown (My University, 2021)
Objectives To determine trends in clinical practice for individuals with DSD requiring gonadectomy. Design Retrospective cohort study. Methods Information regarding age at gonadectomy according to diagnosis; reported sex; time of presentation to specialist centre; and location of centre from cases reported to the International DSD Registry and who were over 16 years old in January 2019. Results Data regarding gonadectomy were available in 668 (88%) individuals from 44 centres. Of these, 248 (37%) (median age (range) 24 (17, 75) years) were male and 420 (63%) (median age (range) 26 (16, 86) years) were female. Gonadectomy was reported from 36 centres in 351/668 cases (53%). Females were more likely to undergo gonadectomy ( n  = 311, P  < 0.0001). The indication for gonadectomy was reported in 268 (76%). The most common indication was mitigation of tumour risk in 172 (64%). Variations in the practice of gonadectomy were observed; of the 351 cases from 36 centres, 17 (5%) at 9 centres had undergone gonadectomy before their first presentation to the specialist centre. Median age at gonadectomy of cases from high-income countries and low-/middle-income countries (LMIC) was 13.0 years (0.1, 68) years and 16.5 years (1, 28), respectively ( P  < 0.0001) with the likelihood of long-term retention of gonads being higher in LMIC countries. Conclusions The likelihood of gonadectomy depends on the underlying diagnosis, sex of rearing and the geographical setting. Clinical benchmarks, which can be studied across all forms of DSD will allow a better understanding of the variation in the practice of gonadectomy.
Gonadectomy in conditions affecting sex development